Student acceptance of ChatGPT in higher education: A mixed-method study of attitudes, intentions, and concerns (Journal of Applied Learning and Teaching, 2025)
ChatGPT has become a widely accessible tool for university students, yet the factors influencing its acceptance or hesitation remain underexplored. This study investigates undergraduate students’ attitudes, intentions, and behaviors toward using ChatGPT in higher education, using a mixed-method design with the Technology Acceptance Model (TAM). A revised TAM survey, incorporating constructs such as Perceived Ease of Use, Perceived Usefulness, Attitude, Behavioral Intention, and Actual Use, was administered to 687 students across nine institutions during December 2024. Results indicate that students who perceive ChatGPT as useful exhibit more positive attitudes, leading to stronger Behavioral Intentions and higher Actual Use for academic tasks outside the classroom. Additionally, open-ended responses and interviews highlighted both benefits and concerns. Key benefits included time savings, ease of information gathering, and enhanced creativity. Concerns focused on a lack of understanding of ChatGPT’s functionalities, fear of over-reliance, mistrust of generated content, and risks to academic integrity. These findings suggest that while many students recognize ChatGPT’s potential as a study aid, challenges related to user education and ethical use must be addressed. This study contributes to the growing discourse on AI integration in higher education by offering evidence-based insights and practical strategies for leveraging ChatGPT as an effective, ethical tool to support student learning in higher education.